Larotrectinib: A Novel Tumor-Agnostic Neurotrophic Tropomyosin Receptor Kinase (NTRK) Inhibitor in Advanced Solid Tumors - Dhanushkodi, Manikandan; Bajpai, Jyoti (Indian Journal of Medical and Paediatric Oncology, 2021)
Larotrectinib and entrectinib are highly selective, potent tropomyosin receptor kinase fusion inhibitors. It is U.S. Food and Drug Administration approved for the treatment of adult and pediatric advanced solid tumors with neurotrophic tropomyosin receptor kinase fusion genes who are refractory to standard systemic therapy. The response rate was ~80% and was rapid and durable. The median progression-free survival was 28 months. The side effects include anemia, weight gain, hepatotoxicity, and neuropsychiatric manifestations. Phase 3, randomized controlled trials are warranted to assess survival benefit.
Keywords: larotrectinib; NTRK inhibitor; tumor agnostic therapy